The Real Reinvestment Rate Assumption as a Hidden Pitfall - Mária Illés (Theory, Methodology, Practice, 2016)
The paper explores a few hidden problems of the reinvestment rate assumption. The automatism of net present value method creates and applies a very special reinvestment rate assumption. This assumption does not disturb the evaluation of investment projects with orthodox cash flow patterns. However, in the case of unorthodox cash flow patterns, automatism constructs a serious mistake in the calculations. In this case, the net present value provides wrong information about the economic efficiency. However, according to the general academic opinion, the net present value method is suitable for evaluation in the case of unorthodox cash flow patterns as well, as there can be only one net present value as opposed to the opportunity of several internal rates of return. The paper sets out to prove that this way of evaluation is wrong, and works out a solution based on the real economic basis.